Involving Technical University Learners in an EFL Reading Course: A Socio-cultural and Cooperative Approach - Ming, Yueh Shen (INTI International University, 2007)
This paper reports the results of a reading course theoretically underpinned by socio-cultural theory as well as the notion of cooperative learning. The aim of the instructional program was to engage the low proficiency and low-motivated EFL learners in reading by exposing them to several types of activities when reading Ann Holm’s novel, “I’m David” as the reading text. Data were collected from threading logs and a student perception questionnaire to investigate the effectiveness of learning, learners’ attitude and belief towards reading, and learners’ reactions towards the class activities. Results indicated that learners’ reactions to this designed course were positive and the learners benefited not only in linguistic development, but also in personal growth. Some pedagogical implications and the limitations were also discussed.